Phase II evaluation of IPI-926, an oral Hedgehog inhibitor, in patients with myelofibrosis. Issue 7 (July 2015) - Sasaki, Koji; Gotlib, Jason R.; Mesa, Ruben A.; Newberry, Kate J.; Ravandi, Farhad; Cortes, Jorge E.; Kelly, Patrick; Kutok, Jeffery L.; Kantarjian, Hagop M.; Verstovsek, Srdan
Abstract The clinical safety and efficacy of IPI-926 was evaluated in 14 patients with myelofibrosis in a phase II study. Patients received 160 mg IPI-926 orally in continuous 28-day cycles. The median treatment duration was 5.1 months, and all patients had discontinued treatment by 7.5 months. Nine patients discontinued due to lack of response as determined by the treating physician, two after developing acute leukemia and one due to disease progression/loss of response. Twelve patients had slight reductions in spleen size (less than 50% from baseline), but symptoms did not improve consistently. One patient achieved transfusion independence lasting 5 months. Reductions in GLI1 mRNA and protein levels, JAK2V617F allele burden, degree of fibrosis or cytokine levels were observed in some patients, but were not significant when evaluated for the cohort. Low-grade gastrointestinal/liver abnormalities were the most common toxicities. The results did not support continued evaluation of IPI-926 as a monotherapy in myelofibrosis.